Analysis of Injury Patterns in Railway Track Death and their correlation with Manner of Death in the Bhopal Region- An Autopsy Based Study - Khilji, S; Verma , PK; Patel, D; Chouksey, V (Journal of Indian Academy of Forensic Medicine, 2024)
Cases of deaths due to railway injuries are important in respect to medico- legal investigation to find out the underlying cause and manner of death. This study was undertaken for assessment of load and to study the cases of railway fatalities for the pattern of injuries sustained, manner and cause of death with the evaluation of factors responsible for such events and to suggest recommendations for curbing such events. The primary goal of this study, which focused on 107 railway-related deaths at the Gandhi Medical College in Bhopal, was to identify the cause of death from the pattern of injuries. In our study we found 91.6% of the 107 victims were men, while 8.4% were women. Most victims (54.2%) were in the age range of 21 to 40. 90.7% of 107 incidents resulted in spot deaths. In case of the visceral injuries brain and liver are maximum affected organs. Externally abrasion and contusions are commonly seen in both type of cases, abrasion found in almost 100 percent cases. Laceration and crushed injuries are more commonly seen in accidental cases and decapitation seen only in suicidal cases. There were no homicide cases in this study; instead, 66.4% of the cases were accidental and 33.6 percent of the cases were suicide. Our study’s analysis suggests that after detailed examination of spot and body position at the scene of crime, closely checking for injury pattern and their frequency in same type of cases, obtaining detailed history from police, relatives and eye witnesses we can opine a possible manner of death.